Intensive systemic chemotherapy is effective against recurrent malignant Brenner tumor of the ovary: An analysis of 10 cases within a single center - Ji-Hyun Han; Dae-Yeon Kim; Shin-Wha Lee; Jeong-Yeol Park; Jong-Hyeok Kim; Yong-Man Kim; Young-Tak Kim; Joo-Hyun Nam (Elsevier, 2015)
Objective: Malignant Brenner tumors (MBTs) of the ovary are very rare, and their definition, biology, and treatment modality have not been established. This study investigated the clinical characteristics of MBTs and the importance of chemotherapy for recurrent disease. Materials and methods: We conducted a retrospective analysis of 10 patients with MBT of the ovary treated at a single tertiary center from 1991 to 2013. Results: The median age was 55.5 years (range, 37-68 years). Nine of the 10 patients were symptomatic. The median size of the ovarian tumors was 10.5 cm (range, 2.5-25.0 cm). The cancer antigen-125 level was elevated in three patients. Six patients had a stage I tumor, one had a stage II tumor, two had a stage III tumor, and one had a stage IV tumor. Six patients received systemic adjuvant chemotherapy after surgery. The mean follow-up duration was 54.5 months (range, 8-173 months). Disease recurrence occurred in four of the 10 patients. The median time to recurrence was 11 months (range, 9-18 months). Two patients with locoregional recurrence showed favorable results after chemotherapy, regardless of the initial stage of the tumor. The patient with the stage IIIC tumor is alive at 13 months after recurrence on current chemotherapy. The patient with the stage IV tumor showed no evidence of the disease > 12 years after the last chemotherapy. Lastly, two patients with distant recurrence died after showing a long-term survival of 49 months and 88 months, respectively, after recurrence and intensive chemotherapy. Conclusion: Our results showed that systemic chemotherapy is beneficial in patients with recurrence of a primary MBT of the ovary, especially in the locoregional recurrence.